Pelatihan dan Pendampingan Digital Marketing bagi Pelaku Usaha Rumah Makan untuk Meningkatkan Daya Saing - Nurhayati; Arisman; Nuraina; Suminar Ariwibowo; Nanda felani Baihaqi; Syahrial Sitorus (Cattleya Darmaya Fortuna, 2026)
The culinary business sector, especially small and medium-scale restaurants, faces increasingly competitive challenges in the digital era. Many restaurant business owners still rely on conventional promotional methods and have not optimally utilized digital technology to expand market reach and improve competitiveness. This community service activity was carried out with the aim of providing training and mentoring related to digital marketing strategies for restaurant business actors. The methods used in this activity include observation, socialization, training, mentoring, and evaluation. The training materials covered the use of social media, digital content creation, online promotion strategies, customer engagement, and the utilization of digital platforms such as Instagram, WhatsApp Business, Google Maps, and food delivery applications. The results of this activity showed an increase in participants’ understanding and skills in managing digital promotions, creating attractive content, and utilizing online platforms to support business development. Through this activity, restaurant business actors are expected to be able to improve service quality, expand market reach, and strengthen business competitiveness in the digital era.